Malaria "Diagnosis" and Diagnostics in Afghanistan. (May 2013) - Reynolds, Joanna; Wood, Molly; Mikhail, Amy; Ahmad, Tamanna; Karimullah, Karimullah; Motahed, Mohibullah; Hazansai, Anwar; Baktash, Sayed Habib; Anwari, Nadia; Kizito, James; Mayan, Ismail; Rowland, Mark; et al.
In many malaria-endemic areas, including Afghanistan, overdiagnosis of malaria is common. Even when using parasite-based diagnostic tests prior to treatment, clinicians commonly prescribe antimalarial treatment following negative test results. This practice neglects alternative causes of fever, uses drugs unnecessarily, and might contribute to antimalarial drug resistance. We undertook a qualitative study among health workers using different malaria diagnostic methods in Afghanistan to explore perceptions of malaria diagnosis. Health workers valued diagnostic tests for their ability to confirm clinical suspicions of malaria via a positive result, but a negative result was commonly interpreted as an absence of diagnosis, legitimizing clinical diagnosis of malaria and prescription of antimalarial drugs. Prescribing decisions reflected uncertainty around tests and diagnosis, and were influenced by social- and health-system factors. Study findings emphasize the need for nuanced and context-specific guidance to change prescriber behavior and improve treatment of malarial and nonmalarial febrile illnesses.